Clinical presentation of psychotic experiences in patients with common mental disorders attending the UK primary care improving access to psychological therapies (IAPT) Programme - Wiedemann, Anna; Stochl, Jan; Russo, Debra; Patel, Ushma; Ashford, Polly-Anna; Ali, Naima; Jones, Peter B; Perez, Jesus (Journal of affective disorders, 2024)
BACKGROUND: Improving Access to Psychological Therapies (IAPT) services address anxiety and depression in primary care, with psychotic disorders typically excluded. Our previous research found 1 in 4 patients report distressing psychotic experiences (PE) alongside common mental disorders, yet little is known about their clinical presentation and impact on recovery. METHODS: We used the Community Assessment of Psychic Experiences - Positive Scale (CAPE-P15) to assess the clinical presentation and symptomatic profile of PE within IAPT settings across three National Health Service (NHS) trusts, serving a diverse population in Southern England. We identified different classes based on the reported PE frequencies using latent class analysis. RESULTS: A total of 2042 IAPT patients completed the CAPE-P15. The mean age was 39.8 (±15.3) years. We identified five distinct classes of symptom profiles, findings that PE were common, especially self-referential and persecutory ideas. Prevalence and intensity increased across classes, extending to bizarre experiences and perceptual abnormalities in the fifth and least common class. Perceptual abnormalities were a strong indicator of symptom severity, with patients being the least likely to achieve recovery by the end of treatment. LIMITATIONS: Data were collected during a service evaluation. Replication of these findings across other IAPT services could prove beneficial. We did not collect information on negative PE. CONCLUSIONS: Patients seeking treatment for anxiety and depression in primary care commonly experience a wide range of positive PE. Self-referential and persecutory ideation were prevalent; perceptual abnormalities were infrequent. Providing information about prevalence and tailoring therapy may help reduce patient distress.
Keywords: Psychotic Disorders; Cognitive Behavioral Therapy; psychotické poruchy; Improving access to psychological therapies; Humans; státní lékařství; Anglie; primární zdravotní péče; Common mental disorder; lidé; Health Services Accessibility; kognitivně behaviorální terapie; Primary Health Care; dostupnost zdravotnických služeb; NHS talking therapies; Depression; State Medicine; Psychotic experiences; dospělí; Adult; Anxiety; England; duševní poruchy; Mental Disorders